The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.42133
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Usefulness of ChatGPT in Oral and Maxillofacial Radiology

Abstract: Aim This study aimed to evaluate the potential usefulness of Chat Generated Pre-Trained Transformer-3 (ChatGPT-3) in oral and maxillofacial radiology for report writing by identifying radiographic anatomical landmarks and learning about oral and maxillofacial pathologies and their radiographic features. The study also aimed to evaluate the performance of ChatGPT-3 and its usage in oral and maxillofacial radiology training. Materials and methods A questionnaire consisting of 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Other studies have highlighted a number of existing issues that can be resolved through advanced training and development of the algorithms, such as maintaining context, emotional intelligence, and real-time multimodal interactions [ 21 ]. Despite the general acceptance of integrating chatbots into healthcare practice, healthcare providers from various fields still express a cautious behavior insinuating the lack of complete trust in chatbots and the necessity of human supervision, which can be justified due to the current existence of a number of limitations, including the aforementioned [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have highlighted a number of existing issues that can be resolved through advanced training and development of the algorithms, such as maintaining context, emotional intelligence, and real-time multimodal interactions [ 21 ]. Despite the general acceptance of integrating chatbots into healthcare practice, healthcare providers from various fields still express a cautious behavior insinuating the lack of complete trust in chatbots and the necessity of human supervision, which can be justified due to the current existence of a number of limitations, including the aforementioned [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for wrong or inaccurate answers (and their deviation from the established "gold standard") could be attributed to the fact that the prompts must be very specific for the results to be accurate, as LLMs' outputs are sensitive to the level of detail in the question; therefore, some questions were probably not phrased accurately enough for the LLMs to correctly perceive them [38]. In addition, in medical and dental AI, deficiencies in the representativeness of the training data sets (different for the different LLMs) may result in inadequate answers [39].…”
Section: Principal Findings and Explanationsmentioning
confidence: 99%
“…Mago and Sharma [38] asked ChatGPT-3 80 questions on oral and maxillofacial radiology, related to anatomical landmarks, oral and maxillofacial pathologies, and the radiographic features of pathologies, and the answers were evaluated by a dentomaxillofacial radiologist. They concluded that ChatGPT-3 was overall efficient and can be used as an adjunct when an oral radiologist requires additional information on pathologies; however, it cannot be the main reference source.…”
Section: Comparison With Relevant Literaturementioning
confidence: 99%
“…In the realm of radiology practice, AI and in particular LLMs, such as ChatGPT 3.5 Turbo and GPT-4, have shown extraordinary proficiency in comprehension, production, and manipulation of human language, demonstrating great potential also for the generation of structuring radiological reports ( 5 , 10 - 12 ). They are able to analyze lengthy and descriptive radiology reports and distill essential information into concise structured format.…”
Section: Introductionmentioning
confidence: 99%